Эволюция природных комплексов и смена типов верхнепалеолитических поселений на заключительных этапах последнего оледенения (по материалам стоянок Посеймья Быки) - Ахметгалеева, Н.Б. (Археологический альманах, 2009)
This work is dedicated to evolution of natural complexes and change of types of sites on the Upper Palaeolithic complex of Byki on the final stage of the Late Glacial. The sites are located on the left bank of Seim River (Russia). To solve this problem the complex investigations of the Upper Palaeolithic Byki site (dated by C14 from 25200 to 16000 B.P.) has been proposed. In the Seim River basin during the final stage of the Late Glacial the existence of different by structure and functional features settlements has been confirmed. We have noticed variability of camp types which cannot be explained by a different seasons of their occupation. Also, the evidence of definite evolution of natural complexes which could cause the change of subsistence strategy and the evolution of Upper Palaeolithic settlement’ types has been studied.